ChemInform Abstract: Rhodium(III)‐Catalyzed Regioselective C—H Alkenylation of Phenylphosphine Sulfides. Issue 7 (29th January 2015) - Yokoyama, Yuki; Unoh, Yuto; Hirano, Koji; Satoh, Tetsuya; Miura, Masahiro
Abstract An effective method for the Rh‐catalyzed ortho‐alkenylation of phenylphosphine sulfides is developed using a P=S group‐directed C‐H bond cleavage.